The influence of Malay proverb illustration among primary students / Siti Zulaikha Sheikh Ismail - Sheikh Ismail, Siti Zulaikha (2022)
Peribahasa or Malay proverb was characterized by reflecting the profound thought and imagination of the Malay people from time immemorial. The Malay proverbs also highlights the social and moral values. They thoughts are conveyed in explicit and implicit Malay proverbs. However, the usage of Malay proverb in everyday conversation and formal event nowadays are rapidly dwindling. Its usage has begun to bleach in the Malaysia society especially young generation. That’s made the reason why most of primary school students experience difficulty in process learning the proverb. Anyway, in this modern world many party involved in creating things that have advantages for us. This includes illustrator, graphic design and animator in trying their best to produce a attractive visual eithers it’s a game, application or a book. This paper will find out if proverb book that full with visual illustration will attract primary students to have their interest in learning Malay proverb.